The Subtitling Strategies of Katherine Wyler’s Utterances in The Diplomat TV Series Season 02 Episode 01 - Sunarti Desrieny Tambunan (Asosiasi Dosen Muda Indonesia, 2025)
The primary objective of this research is to discover the subtitling strategies employed in translating Katherine Wyler's utterances in The Diplomat TV Series Season 02 Episode 01 from English into Indonesian using Gottlieb's theory. Because the findings are not reached through statistical procedures or other methods of quantification, thus, this research used descriptive and qualitative. Katherine Wyler articulated a total of 155 utterances. In accordance with Gottlieb's theoretical framework, seven out of ten strategies have been discovered. The findings of the study revealed 171 data related to subtitling strategies. The first strategy is transfer with 66 data, followed by condensation strategy with 40 data. Then paraphrase strategy with 35 data, expansion strategy with 16 data, imitation strategy with 7 data, deletion strategy with 4 data, and decimation strategy with 3 data. The findings of the research indicate that the most frequently employed strategy is transfer. Furthermore, three strategies were not discovered. They are resignation, transcription, and dislocation.